L'homme et la brute au XVIIe siècle Une éthique animale à l'âge classique ? - Bedon, Marine (La croisée des chemins, 2022)
Anyone seeking the premise of animal ethics in the 17th century will undoubtedly be disappointed. "Brute beasts", as they were then called, were excluded from the sphere of obligations, and not just by a few cartesian mechanics. A large number of authors maintained that animals feel or that they have a soul which is not that different from ours. Many were outraged at human cruelty towards them. Some claimed that they are endowed with reason, sometimes using them as a point of comparison in order to belittle human pride. They were even given rights. The diversity of positions, representations and arguments rarely coincides with the charges we lay against early modern philosophy today. Not all of these authors are Cartesians and the animal-machine theory is perhaps a little more than the effect of mere prejudice. None, however, envisage an ethical, moral or legal link with animals. Paradoxically, those most free from anthropocentrism grant them rights, but most radically claim the absence of any ethical link between men and animals. Reading these works from another age in the light of a question they could not formulate challenges what we consider self-evident today and provides us with resources to pose and solve problems that are ours, not theirs.